(untitled) (Indonesian Theological Justice Review, 2025)
The Indonesian Church has played a significant role in political and social justice movements, particularly in the post-Suharto era. This paper provides a theological analysis of the Church’s involvement in advocating for human rights, political reform, and social justice in Indonesia. The study traces the historical development of the Church’s engagement with political movements, starting with its stance against the authoritarian regime and continuing into its contemporary involvement in issues such as religious freedom, democracy, and economic inequality. The paper examines how Christian theological principles—such as the teachings of Jesus on justice, mercy, and the dignity of the human person—have shaped the Church’s advocacy for marginalized groups, including ethnic minorities, religious dissidents, and the poor. It also evaluates the Church’s role in shaping public discourse on human rights and social justice, particularly through social programs, educational initiatives, and partnerships with civil society organizations. The research argues that the Church’s involvement in these movements demonstrates the relevance of Christian theology in shaping Indonesia’s political and social landscape. It concludes by recommending ways in which the Church can continue to contribute to justice and human rights efforts, particularly by fostering deeper interfaith dialogue and engaging in cross-cultural alliances.